2002
DOI: 10.1136/bjsm.36.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendinopathy: some aspects of basic science and clinical management

Abstract: Achilles tendinopathy is prevalent and potentially incapacitating in athletes involved in running sports. It is a degenerative, not an inflammatory, condition. Most patients respond to conservative measures if the condition is recognised early. Surgery usually involves removal of adhesions and degenerated areas and decompression of the tendon by tenotomy or measures that influence the local circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
318
0
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(346 citation statements)
references
References 157 publications
8
318
0
9
Order By: Relevance
“…This has to be taken into account during rehabilitation after injury and surgery. The maturation and remodeling phase of tendon healing is reported to occur from 3 weeks to 12 months after tendon rupture (Enwemeka, 1989b, Leadbetter, 1992, Józsa and Kannus, 1997, Kannus et al, 1997c, Kader et al, 2002. A patient with an injury to the Achilles tendon must therefore expect a recovery time of 3 months to a year, and sometimes longer, depending on the severity of the injury.…”
Section: Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…This has to be taken into account during rehabilitation after injury and surgery. The maturation and remodeling phase of tendon healing is reported to occur from 3 weeks to 12 months after tendon rupture (Enwemeka, 1989b, Leadbetter, 1992, Józsa and Kannus, 1997, Kannus et al, 1997c, Kader et al, 2002. A patient with an injury to the Achilles tendon must therefore expect a recovery time of 3 months to a year, and sometimes longer, depending on the severity of the injury.…”
Section: Metabolismmentioning
confidence: 99%
“…The difference appears to be that growing animals respond by increasing the size and weight of tendons, whereas the mature animals respond by improving the structure of the tendon with exercise (Kannus et al, 1997c). However, it has been suggested that physical exercise performed in excess is the main pathological stimulus in overuse damage to the tendon (Leadbetter, 1992, Józsa and Kannus, 1997, Kader et al, 2002, Paavola et al, 2002a. The human Achilles tendon not been studied to the same degree, but found that intensively trained athletes had a greater cross-sectional area of the Achilles tendon compared with controls.…”
Section: Effect Of Exercise On Tendonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Painful tendon disorders are a major problem in competitive and recreational sports [10,13,14,18]. Over the last decade, several studies have provided the opportunity to develop novel therapeutic strategies [4-9, 17, 19, 23, 26].…”
Section: Introductionmentioning
confidence: 99%